ARGO: ARctic greenhouse Gas Observation metadata version 1 - J. Vogt; M. M. T. A. Pallandt; L. S. Basso; A. Bolek; K. Ivanova; M. Schlutow; G. Celis; M. Kuhn; M. Mauritz; E. A. G. Schuur; K. Arndt; A.-M. Virkkala; et al. (Earth System Science Data)
Our understanding of how rapid Arctic warming and permafrost thaw affect global climate dynamics is restricted by limited spatiotemporal data coverage due to logistical challenges and the complex landscape of Arctic regions. It is therefore crucial to make best use of the available observations, including the integrated data analysis across disciplines and observational platforms. To alleviate the data compilation process for syntheses, cross-scale analyses, Earth system models, and remote sensing applications, we introduce the ARctic greenhouse Gas Observation metadata version 1 (ARGO), a new meta-dataset comprised of greenhouse gas observations from various observational platforms across the Arctic and boreal biomes within the polar region of the Northern Hemisphere. ARGO provides a centralised repository for metadata on carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) measurements and is linked to an interactive online tool (https://www.bgc-jena.mpg.de/argo/, last access: 6 May 2025). This tool offers prompt metadata visualisation for the research community. Here, we present the structure and features of ARGO, underscoring its role as a valuable resource for advancing Arctic climate research and guiding synthesis efforts in the face of rapid environmental change in northern regions. The ARGO meta-dataset is openly available for download at Zenodo (https://doi.org/10.5281/zenodo.13870389; Vogt et al., 2024a).